Kontribusi dan Fungsi Seni Budaya dalam Pendidikan sebagai Wadah Pembentukan Karakter Siswa - Muhammad Rapi (Paedagogik, 2013)
In connection with the development and progress of the age, in addition to science and technology, the arts is one of the cultural elements are also progressing and not merely touching the dimension of art, but also the entire realm of culture. It can be felt that the art inherent characteristic of a culture, as art belong together and have a common set of values, ideas, and rationale for the behavior. In addition, art is made with reference to the actions of individuals as well as individuals to understand and comprehend the group. Art has a meaning to life, both personally and as a group. Furthermore, another characteristic is that art and transformation learned from one generation to the next. Together with the aspects cif science and technology aspects, art is one aspect that can nor be ignored in the contribution and its function in the formation of character and artistic aspects character. Throught, individuals, and groups, as well as a community, can provide characteristics in existence as a particular community. Indonesiaan, for example, can be recognized by other States as art, art is universal in addition, also has ethnic character, the character of the trust, individual character, and other characters attached to it. Asafield of study, the arts and arts education, have a basic concept that needs to be lived. Concept art is, art as beauty, art as entertainment, art as a medium of communication,( art as art as imitation and expression- While the concept of art education (in art education), is, through the art students were given the experience of beauty, learners are given the experience in art and enjoyment factor is a major consideration that must be considered, learners are given the experience of* art can provide an opportunity to communicate ideas or ideas, students are trained to be able to mimic the natural shape accurately observed. And through the process of art education students are trained to express ideas in the form of art. The approach used is known to express yourself approach to free expression.